Effect of Seed Extracts of Vigna unguiculta and Hordeum vulgare on Kidney Homogenate and Rat Kidney Injury Molecule-1 in Ethylene Glycol and Ammonium Chloride Induced Urolithasis in Rats - Patel, Monika; Raval, SK; Modi, RJ (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The experiment was carried out to study the therapeutic efficacy of aqueous, alcoholic, and biherbal extracts of Vigna unguiculata (VU)and Hordeum vulgare (HV) in ethylene glycol and ammonium chloride-induced urolithiasis in female Wistar rats. Rats were dividedinto 14 groups, each of 6 rats, except the lithiatic control group, which consisted of 8 rats. Group I and II served as lithiatic and vehiclecontrol, respectively. In group I and III to XIV urolithiasis were induced by administration of 0.75 % (v/v) ethylene glycol and 2% (w/v)ammonium chloride along with drinking water for 28 days. Group II was given 0.5% sodium bicarbonate. After the 28th day, the ratsof urolithiatic treatment Groups III to XIV were given aqueous and alcoholic seed extracts of VU and HV @ 200 mg/kg and 300 mg/kgb.wt. orally as either single extract or combination as biherbal extracts (1:1) in 0.5 % sodium bicarbonate for another 35 days usingsyringe and rat gavage needle. Blood samples were collected twice: on the 28th day of induction of urolithiasis and 63rd day experiment/herbal treatment. Significantly (p
Keywords: Biherbal extract; Ethylene glycol; Hordeum vulgare; Urolithiasis; Vigna unguiculata; Wistar rat.